2018
DOI: 10.1055/s-0038-1675796
|View full text |Cite
|
Sign up to set email alerts
|

Posteromedial versus Anteromedial Hamstring Tendon Harvest for Anterior Cruciate Ligament Reconstruction: A Retrospective Comparison of Accidental Gracilis Harvests, Outcomes, and Operative Times

Abstract: Hamstring autografts are frequently harvested for anterior cruciate ligament reconstruction (ACLR), traditionally through the anteromedial (AM) approach. Recently, a posteromedial (PM) approach has been described. The primary purpose of this study was to compare rates of unintentional gracilis (Gr) harvest or premature tendon amputation with these approaches. We also sought to compare operative times and patient-reported outcome measures (PROMs) between both groups and between those with only semitendinosus (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Detailed information about the included studies can be found in Tables 1 and 2 . 17 18 19 20 21) For an overview of the study selection process, refer to Fig. 1 in the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed information about the included studies can be found in Tables 1 and 2 . 17 18 19 20 21) For an overview of the study selection process, refer to Fig. 1 in the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…There were 5 studies 17 18 19 20 21) comparing anteromedial and posteromedial approaches for hamstring harvest that reported occurrences of saphenous nerve injury. The overall occurrences of saphenous nerve injury in the anteromedial and posteromedial techniques for hamstring harvest were 10.2% and 0.4%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Amputation during hamstring graft harvesting is rare, but when it occurs, the common cause is insufficient removal of the accessory branches of the gracilis and semitendinosus tendons [ 4 ]. The accessory attachments of the tendons cause transection of either the gracilis or semitendinosus tendon by misdirecting the tendon stripper, resulting in a shorter graft.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) reconstruction is one of the most common operations in sports medicine [ 1 ], for which either a hamstring tendon or patellar tendon graft is commonly used [ 2 , 3 ]. There are some possible complications during or after hamstring graft harvesting such as premature graft amputation [ 4 ], medial collateral ligament injury [ 5 ] and infrapatellar branch of the saphenous nerve injury [ 6 , 7 ]. Premature graft amputation can occur by inadequate removal of the accessory branches of the hamstring tendons, poor surgical technique and/or too sharp tendon stripper [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shu et al [ 43 ] retrospectively reviewed 29 patients who underwent a posteromedial harvest as described by Wilson et al [ 40 ]. Among these patients, 22 underwent an anteromedial harvest.…”
Section: Graft Harvestingmentioning
confidence: 99%